Mystical Veiled Configuration of Agile Operant Resources for Profitability in Family Businesses of Pakistan - Waheed, Mehreen; Kausar, Abdul Rashid; Sana, Sundas (European Journal of Family Business, 2023)
Resources act as an arm which often facilitates firm’s sustainable performance in volatile business markets. Few studies have emphasized the agile operant resources that propel family-owned firm’s profitability. The aim of this article is to show the concealed role of agile operant resources of firm owners that expedite family-owned businesses in profitability to ensure a firm’s sustainability. This research uses relativistic perspective based on interpretive worldview. For data collection, purposive sampling is used. While directing interviews, open-ended questions (interview guide) along with observations are used. Abductive research accompanied by Gioia methodology has been utilized for broader themes of discussion. The findings indicated relationship proneness, reputational resources, religious resources, agile soft skills, performance efficiency and excellency as hidden agile intangible resources which facilitate family firms of catering profitability. The paper presents a conceptual framework that highlights how family-owned firms can ensure profitability. The proposed research framework contributes to the present literature of family-owned firms by inspecting the mystical role of agile resources. It opens new avenues for practitioners to work on these resources that support to enhance profitability.